Energy and Delay Constrained Packet Transmission MAC Protocol for Wireless Sensor Networks - Young Lee, Jin; Cheol Kim, Seong; Yun Kim, Hye (International Journal of Engineering and Technology, 2018)
In this paper, we present an energy and time constrained packet transmission MAC Protocol which we call ED-MAC for event-driven applications such as fire detection in wireless sensor networks (WSNs). In this kind of WSNs, sensor nodes send a burst data when there is an event in the measuring field. These events are usually critical, so the measured burst data should be transmitted in limited time to their final destination node, sink node. Therefore, the packet transmission delay is considered to be a crucial requirement in event-driven applications. The ED-MAC protocol reduces the packet transmission delay and average node energy consumption in comparison to existing related MAC protocols.Â